Aktivitas Antibakteri Epigallocatechin Gallate (EGCG) Teh Hijau pada Bakteri Gram Positif dan Bakteri Gram Negatif - Afifah, Syafira Hasna; Apriliana, Ety; Setiawan, Gigih; Berawi, Khairun Nisa (CV. Jasa Sukses Abadi, 2024)
Epigallocatechin gallate (EGCG) is a catechin compound found in green tea and is known for its various health benefits, including antioxidant, anti-inflammatory, and antibacterial activity. Research on the antibacterial effects of EGCG shows that this compound has significant potential in inhibiting the growth of various pathogens, both Gram-positive and Gram-negative bacteria. Gram-positive bacteria, such as Staphylococcus aureus and Streptococcus pneumoniae, are more sensitive to EGCG than Gram-negative bacteria. The antibacterial mechanism of EGCG in Gram-positive bacteria involves disrupting cell membrane integrity and inhibiting biofilm formation, while in Gram-negative bacteria, EGCG can increase the permeability of the outer membrane and increase the penetration efficiency of antibiotics. However, the main challenge in using EGCG against Gram-negative bacteria is the structural barrier present in the outer membrane, which limits the penetration of the compound. The use of EGCG in combination therapy with antibiotics shows great potential in overcoming antibiotic-resistant infections, strengthening antibacterial activity, and reducing side effects. Although EGCG shows promise as an antibacterial therapy, challenges related to bioavailability, stability, and formulation need to be overcome to optimize its potential in the treatment of difficult-to-treat bacterial infections.